Implementasi Metode Profile Matching untuk Penentuan Mahasiswa Berprestasi - Siagian, Edward Robinson (LPPM UNIKA Santo Thomas Medan, 2020)
Decision support systems developed at the beginning of the era of distributed computing and began to develop in the 1960-1970s, as a result of a number of other factors: hadware and software technology, research efforts by academics from universities, began to grow awareness of the support of a decision and the desire to obtain better information. In this study, a case will be raised, which is looking for the best alternative based on student competence in the